Diet and nutritional status in Peru - Collazos Chiriboga, Carlos (1960)
Peru, located in the central and western part of South America, is a unitary state with a republican form of government and 10'213, 000. It has a surface area of ​​1'311030 Km2 and two natural axes, the Pacific Ocean and the Andes Mountains, which differentiate its territory into three geographic regions: the coast, mountain and forest. The three Peruvian regions are not only geographical individuality, but also economic and social. DE: So, to study the nutritional status of the Peruvian family, the Ministry of Public Health and Social Welfare through the Institute of Nutrition of the American Cooperative Public Health, has had to make a series of studies in selected populations carefully be representative of the Costa, Sierra and Selva.